Formative Research: Using a Community-Based Participatory Research Approach to Develop an Oral Health Intervention for Migrant Mexican Families. Issue 3 (May 2017) - Finlayson, Tracy L.; Asgari, Padideh; Hoffman, Lisa; Palomo-Zerfas, Ana; Gonzalez, Martha; Stamm, Nannette; Rocha, Maria-Isabel; Nunez-Alvarez, Arcela
Oral health is a leading unmet health need among migrant families. This article describes the 1-year, community-based participatory research (CBPR) approach employed to plan and develop a Líder Communitario (lay community health worker)–led educational intervention for Mexican migrant adult caregivers and their families in three underserved, remote communities in North San Diego County, California. Four partner organizations collaborated, reviewed existing oral health curricula, and sought extensive input on educational topics and research design from key informants, migrant caregivers, and Líderes Communitarios. Based on community stakeholder input, partners developed a logic model and drafted educational intervention materials. Key informants ( n = 28), including several members from two community advisory boards, ranked program priorities and intervention subgroup population via online survey. Three focus groups were conducted with Líderes Communitarios ( n = 22) and three with migrant families ( n = 30) regarding the oral health program's design and content. Twelve Líderes Communitarios reviewed draft intervention materials during two focus groups to finalize the curriculum, and their recommended changes were incorporated. Formative research results indicated that community stakeholders preferred to focus on adult caregivers and their families. A 5-week educational intervention with hands on demonstrations and colorful visuals was developed, covering the following topics: bacteria and tooth decay, oral hygiene, nutrition, gum disease, and dental services. The CBPR process engaged multiple community stakeholders in all aspects of planning and developing the educational intervention.